Médeia az antik képzőművészetben - Gesztelyi, Tamás (Studia Litteraria, 2017)
Images of Medea were closely linked to sepulchral thoughts from the very beginning, but this meaning was, from time to time, carried by a different motif of her story. In the age of archaic and partly classical style it was the magic of rejuvenation that represented the thought of overcoming death. Obtaining the Golden Fleece as depicted on the late classical South Italian vases as well as on the stucco of early imperial Basilica Sotterranea can be interpreted as a motif of redemption. Imagery of infanticide and rising on a dragon-drawn carriage also appears on South–Italian vases. Just like with funerary objects, sepulchral thoughts cannot be denied in these cases, either, and Medea, holding her dead child depicted on a sculpture fragment from Tarentum is definitely part of a sepulchre. In the Roman imperial period a group of sarcophagi and provincial sepulchres represented Medea, the child-murderer. While several works have been dedicated to unravelling the meaning of the Medea sarcophagi, nearly none has examined the interpretation of the carvings that appeared in provincial art. This is what we have attempted to do while recognising the influence of Euripides’ work in the background, and identifying Medea as a figure embodying several meanings.